Knowledge and skills in information and communication technology (ICT) of academic librarians in Pampanga an assessment - Santos, Rosalyn B. (School of Library and Information Studies, University of the Philippines Diliman, 2006)
The primary objective of the study was to find out the depth of competency in the use of ICT among academic librarians in their present jobs. The study used the descriptive method of research. The questionnaire was used as the primary tool in gathering data along with ocular inspections and personal Interviews.